Three-Component Synthesis of 2-Alkylthiobenzoazoles in Aqueous Media - Chen, Jin-Quan; Guo, Jia; Dong, Zhi-Bing (Synthesis, 2020)
A highly efficient three-component protocol for the synthesis of the 2-alkylthiobenzoazoles is described. Tetramethylthiuram disulfide (TMTD) cyclized with o-aminothiophenols, generating the intermediate 2-mercaptobenzothiazoles, and the successive C–S coupling with halogenated alkanes afforded a series of 2-alkyl-substituted thiobenzothiazoles smoothly in a one-pot process. This procedure could also be utilized for the preparation of 2-alkyl-substituted thiobenzoxazoles and 2-alkyl-substituted thiobenzimidazoles. Inexpensive and easily available starting materials, metal catalyst-free, broad substrate scope, and water as solvent are the features of this protocol.
Keywords: metal-free; synthesis; thiobenzoazole; water; thiuram